Ethics Codes and Sales Professionals' Perceptions of Their Organizations' Ethical Values - Valentine, Sean (Journal of business ethics, 2002)
Most large companies and many smaller ones have adopted ethics codes, but the evidence is mixed as to whether they have a positive impact on the behavior of employees. We suggest that one way that ethics codes could contribute to ethical behavior is by influencing the perceptions that employees have about the ethical values of organizations. We examine whether a group of sales professionals in organizations with ethics codes perceive that their organizational context is more supportive of ethical behavior than sales professionals in companies without codes. After accounting for the effect of several covariates, our results indicated that sales professionals employed in organizations with codes of ethics perceived their work environments to have more positive ethical values than did other sales professionals.